THE JONES STUDIO ARCHITECTURAL COMPANY CREATED A SCHOOL INTERIOR AND THE EFFECT OF COLORS ON CHILDREN IN IT - Saidyusupova , Maftuna (Educational Research in Universal Sciences, 2023)
The architectural firm Jones Studio was selected in 2004 to design a new building for Desiderata Alternative High School. This school is designed for 125 students with developmental disabilities. Its interior and colors are made based on children’s mental state.